2022
DOI: 10.1515/hsz-2022-0230
|View full text |Cite
|
Sign up to set email alerts
|

Heme delivery to heme oxygenase-2 involves glyceraldehyde-3-phosphate dehydrogenase

Abstract: Heme regulatory motifs (HRMs) are found in a variety of proteins with diverse biological functions. In heme oxygenase-2 (HO2), heme binds to the HRMs and is readily transferred to the catalytic site in the core of the protein. To further define this heme transfer mechanism, we evaluated the ability of GAPDH, a known heme chaperone, to transfer heme to the HRMs and/or the catalytic core of HO2. Our results indicate GAPDH and HO2 form a complex in vitro. We have followed heme insertion at both sites by fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…This suggests that NO may improve heme availability and its mobility inside the cell and deserves further study. We also found that the NO-driven heme allocations to apo-IDO1 and apo-TDO relied on formation of a GAPDH–heme complex in the cells, and for IDO1 also relied on Hsp90 function, which means that the NO acts through a mechanism that involves the same machinery that cells normally use to deliver heme to these dioxygenases ( 29 ) and to several other hemeproteins during their maturation ( 51 , 52 , 53 , 54 ). Within this context NO could act in several ways.…”
Section: Discussionmentioning
confidence: 69%
“…This suggests that NO may improve heme availability and its mobility inside the cell and deserves further study. We also found that the NO-driven heme allocations to apo-IDO1 and apo-TDO relied on formation of a GAPDH–heme complex in the cells, and for IDO1 also relied on Hsp90 function, which means that the NO acts through a mechanism that involves the same machinery that cells normally use to deliver heme to these dioxygenases ( 29 ) and to several other hemeproteins during their maturation ( 51 , 52 , 53 , 54 ). Within this context NO could act in several ways.…”
Section: Discussionmentioning
confidence: 69%
“…This suggests that NO may improve heme availability and its mobility inside the cell and deserves further study. We also found that the NO-driven heme allocations to apo-IDO1 and apo-TDO relied on formation of a GAPDH-heme complex in the cells, and for IDO1 also relied on Hsp90 function, which means that the NO acts through a mechanism that involves the same machinery that cells normally use to deliver heme to these dioxygenases (29) and to several other hemeproteins during their maturation (51-54). Within this context NO could act in several ways.…”
Section: Discussionmentioning
confidence: 73%
“…Due to the physical and redox properties of heme, its transport in cells has long been expected to involve a protein chaperone [ [1] , [2] , [3] , [4] , [5] ]. Recently, the glycolytic enzyme GAPDH was shown to fulfill this role by binding mitochondrial heme and through this feature enabling heme delivery to diverse targets including hemoglobin α, β, and γ, myoglobin, tryptophan dioxygenase (TDO), indoleamine dioxygenase 1 (IDO1), soluble guanylyl cyclase (sGC), NO synthases, and heme oxygenase 2 [ [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. In most cases, the heme insertions into these proteins also required the cell chaperone Hsp90 and its ATPase activity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%